ÁDEBIYAT PÁNIN OQÍTÍWDA OQÍTÍWSHÍ HÁM OQÍWSHÍLARDÍŃ KOMPETENTLILIGIN JETILISTIRIW - Uzakova, S.P. (SCIENCE and SOCIETY, 2021)
The article deals with the development of of teachers and students competence in the teaching of literature, and modeled the work of a well-known representative of Karakalpak literature T.Matmurodov and also the competence of teachers and students in the teaching process is studied. It is recommended to use such elements effectively in teaching process.